Under/Over-Investment and Early Renegotiation in Public-Private Partnerships - Daniel Danau; Annalisa Vinella (Center for Economic Studies and ifo Institute (CESifo), 2019)
We consider a public-private partnership in an infrastructure project, which requires specialised expertise during the construction stage for the infrastructure to operationalise. This entails that, after an investment is made to begin building the infrastructure, its construction is completed at a cost, which increases with the investment at an increasing rate, and is higher if the government replaces the firm beforehand. The likelihood of a lower operating cost increases as well with the initial investment. Once the infrastructure is in place, the firm manages it, taking advantage of the (usual) synergy between construction and operation. Given the characteristics of the project, the firm has an incentive to either under-invest or over-invest in early construction, seeking a renegotiation thereafter. We show that, in a renegotiation-proof contract, the marginal cost of the investment facing the government is either above or below the marginal “technological” cost of the investment, at optimum. Accordingly, the resulting investment - although enhanced - is either below or above the efficient level. The contractual payoff of the firm is above its renegotiation payoff in the former case, below in the latter. We further show that when the firm holds private information on the operating conditions, the government may welcome a contractual renegotiation either as a way of containing (avoiding) the distortions due to the informational gap, or as a tool to pass the cost of construction completion onto the firm, or both.
Keywords: D82; H57; H81; 330; public-private partnerships; asset specificity; hold-up; over/under-investment; renegotiation